Level of Knowledge of Menstruation in Supporting Elementary Students Preparation For Menarche - Ida Nurmawati; Feby Erawantini (Faculty of Public Health, Andalas University, 2017)
Nowadays, the first menstrual period in adolescent occurs faster with a lack of their preparation for menarche. This condition make them respond negatively to the menarche by experiencing mixed emotions; fears, shocked, sad, disappointed, embarrassed, worried, and confused. The result of SDKI in 2012 suggested that adolescents need to be provided with sufficient information before their first menstruation. Thus, this research purposes to determine the relationship of knowledge level of elementary school adolescent girls about menstruation and their preparation for menarche. It is an observational study using cross sectional approach. The population of this research is 37 female students of the six graders in SDN Tegalgede 01 Jember Regency who also as the research sample taken by saturated sampling technique. The data is analyzed using Rank Spearman test. The bivariate analysis is done by applying crosstabulation that students with good preparation are found more on students with good knowledge (82,4%) than students with less knowledge (30%). There is a relationship between the students’ level of knowledge about menstruation and their preparation for menarche (p value = 0,026). Based on r = 0,367, there is a passive relationship between the level of knowledge with menarche.